2016
DOI: 10.1002/jcp.25491
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Inhibitor of Metalloproteinase 1 Influences Vascular Adaptations to Chronic Alterations in Blood Flow

Abstract: Remodeling of the skeletal muscle microvasculature involves the coordinated actions of matrix metalloproteinases (MMPs) and their endogenous inhibitors, tissue inhibitor of metalloproteinases (TIMPs). We hypothesized that the loss of TIMP1 would enhance both ischemia and flow-induced vascular remodeling by increasing MMP activity. TIMP1 deficient (Timp1 ) and wild-type (WT) C57BL/6 mice underwent unilateral femoral artery (FA) ligation or were treated with prazosin, an alpha-1 adrenergic receptor antagonist, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…This finding is consistent with a previously published report that EVs from human umbilical vein ECs (HUVECs) contain high levels of TIMP-1 (35). Interestingly, mice that are deficient in TIMP-1 display aberrant microvascular networks, deranged vascular integrity, and diminished vascular remodeling following ischemia (36). Conversely, increased levels of TIMP-1 is associated with poorer prognosis in colorectal cancer with increased liver metastasis (37) and also promoted angiogenesis in a model of lung adenocarcinoma (38).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with a previously published report that EVs from human umbilical vein ECs (HUVECs) contain high levels of TIMP-1 (35). Interestingly, mice that are deficient in TIMP-1 display aberrant microvascular networks, deranged vascular integrity, and diminished vascular remodeling following ischemia (36). Conversely, increased levels of TIMP-1 is associated with poorer prognosis in colorectal cancer with increased liver metastasis (37) and also promoted angiogenesis in a model of lung adenocarcinoma (38).…”
Section: Discussionsupporting
confidence: 92%
“…Baseline Timp1 gene expression is also positively correlated with posttraining strength gains in healthy older adults (16). Although TIMP1 is an inhibitor of matrix metalloproteinases and negative regulator of ECM turnover (6), it can also control vascular remodeling similar to FGF-2 and angiogenin (31,48,51). A recent study by Mandel et al (31) reported significant deficiencies in microvascular content as well as lack of prazosin-mediated arteriogenesis in TIMP1 deficient (Timp1 Ϫ/Ϫ ) mice.…”
Section: Discussionmentioning
confidence: 99%
“…Hindlimb and/or paw blood flow was assessed prior to and immediately post‐ligation surgery (day 0), then subsequently on days 4, 7 and 14 by laser Doppler imaging (Perimed), with mice under light isoflurane anaesthesia and positioned on a warming pad. Relative blood flow was expressed as a perfusion ratio of the ligated limb (paw) and the corresponding region in the contralateral non‐ligated leg . At 4 or 14 days post‐ligation, mice were killed while under isoflurane inhalation anaesthesia and muscles were excised from both ligated and non‐ligated legs.…”
Section: Methodsmentioning
confidence: 99%